Oncological Outcomes of Chromophobe Versus Clear Cell Renal Cell Carcinoma: Results from A Contemporary Turkish Patient Cohort - TİNAY, İLKER (My University, 2024)
Purpose: To compare the oncological outcomes of clear cell RCC (ccRCC), which is common in renal cell carcinomas (RCC), and chromophobic RCC (chRCC), which is less common, and to define the factors affecting survival in the Turkish patient population for both RCC subclassifications. Materials and Methods: Patients with a pathologically confirmed RCC diagnosis after radical or partial nephrectomy in the Turkish Urooncology Association (TUOA), Urological Cancers Database-Kidney (UroCaD-K), were retrospectively reviewed. Patients with ccRCC and chRCC were included in the study. Primary outcomes of this study are recurrence-free survival (RFS), overall survival (OS) and cancer-specific survival (CSS) for each histological subtype. Results: Data from 5300 patients in the TUOA UroCaD-K are reviewed and a total of 2560 patients (2225 in the ccRCC group and 335 in the chRCC group) are included in the final analysis. In the comparison of the groups, tumor size was greater both radiologically and pathologically in chRCC (p=0.019 vs 0.002 respectively). Recurrence-free survival (RFS), overall survival (OS) and cancer-specific survival (CSS) rates are worse in ccRCC subgroup. In the evaluation of risk factors; pathological stage, local invasion and Fuhrmann grade were found to be significant for recurrence in ccRCC. Age, body mass index and pathological stage were the risk factors affecting overall mortality (OM). Pathological tumor size was an independent risk factor for recurrence in chRCC, while age was analyzed as the only parameter affecting OM. Conclusion: chRCC oncological data and OS, CSS and RFS rates were found to be better than ccRCC in the Turkish patient population.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Üroloji Ve Nefroloji; Clinical Medicine (Med); Clinical Medicine; Urology & Nephrology; Üroloji; Urology; Chromophobe RCC; Clear cell RCC; Kidney cancer; Recurrence; Survival